PERSEPSI MASYARAKAT TERHADAP KINERJA PERANGKAT DESA MENGGUNAKAN PERSAMAAN STRUKTURAL - SAPUTRA, I GEDE WIRA HADY; GANDHIADI, G.K.; KENCANA, EKA N. (E-Jurnal Matematika; Vol 11 No 4 (2022), 2022)
The purpose of this research is to determine the factors that influence the perception of rural communities on the performance of the village apparatus in Sawan District, Buleleng, Bali. The method used in this research is partial least square-structural equations modeling (PLS-SEM) method. This research was conducted in 14 villages in Sawan District, Buleleng, Bali within the research period from August to October 2021. Data was obtained through a questionnaire based on the responses of the village community in Sawan District as respondents to the performance of village officials. The number of respondents who responded to the questionnaire in this research is 134 respondents. The results of this research indicate that the village government function, village development function, and village community empowerment function have a significant effect on the performance of the village apparatus, while the village community development function has no significant effect on the performance of the village apparatus.